Ecological civilization and Chinese philosophy - Balchindorjieva O. B. (Humanitarian, 2016)
the author raises the problem of the construction of ecological civilization in China in terms of the definition of «ecological civilization» in the context of traditional Chinese culture in its relationship with the traditional and the modern understanding of harmony and harmonious society, and the development of regulation in the sphere of environmental protection. In the article the analysis of philosophical aspects of this problem is given. The author demonstrates the approach developed by the Chinese scholars to understanding of the ecological civilization as a new stage in the human society’s development coming after industrial society. In conclusion the author proposes to consider this approach a necessary civilizational choice that is to be made by the Chinese society.
Keywords: гармония; цивилизация; harmony; цивилизационный выбор; экологическая цивилизация; китайское общество; civilization; civilizational choice; ecological civilization; Chinese society